Effects of microplastics pollution on the abundance and composition of interstitial meiofauna - Lagos, Ana Milena (2023)
Introduction: Pollution by microplastics is a global problem in marine environments, and impacts microorganisms and ecosystems at several spatial levels. Sandy beaches are depositional environments where microplastics tend to accumulate in large quantities. The co-occurrence of interstitial meiofauna and microplastics in sand grains raises the question on whether the accumulation of microplastics in the sediments affects the abundance and composition of the meiofaunal communities. Objective: To test the hypothesis that microplastics affect the meiofauna of urban sandy beaches. Methods: We studied the three main urban sandy beaches of Santa Marta, Colombia: El Rodadero, Santa Marta Bay, and Taganga. All are similar in morphology and external pressures and differ from other beaches in the region. In April 2019 we collected 81 sand samples, equally distributed in the intertidal zone (upper, mid, and lower intertidal levels). We applied generalized linear models to abundance, and multivariate permutational tests to community composition. Results: We identified 17 taxonomic groups of meiofauna, and microplastic particles (mainly 45-500 micron fibres) evenly distributed across beaches and intertidal levels. There was more meiofauna at the mid intertidal level, and in fine and medium grain sediment. At the lower intertidal level, sites with more microplastics had less meiofauna. Microplastics “explained” 39 % of the variation in meiofaunal communities at lower intertidal levels. Conclusions: The accumulation of microplastics has a negative impact on these meiofaunal interstitial communities. This is not surprising: microplastics occupy the same physical space as these animals, presumably modifying the structure of sediments and the composition of interstitial water. Objective: As a step forward on that direction, we have here analysed the distribution of the abundance of microdebris and major interstitial meiofaunal groups in three urban sandy beaches in Santa Marta region, Colombia, and possible relation among both factors. Methods: We selected the three main urban sandy beaches in Santa Marta, Northern Colombia: El Rodadero, Bahía de Santa Marta, and Taganga. All of them are very similar to each other due to its morfolophy and extern pressions, and differ starkly from other beaches in the region. Sampling was performed in April 2019 with a 81 samples in total equitably distributed in the supratidal zone, intertidal zone, and subtidal zone. In each point, we collected samples for microplastics quantification, meiofaunal community characterization, and granulometric analysis. Results: We extracted a total of 1131 debris particles, dominated by fibres ranging between 45-500 microns. Generalised linear models showed that microdebris were uniformly distributed across beaches and tidal levels, whereas meiofaunal abundances were significantly affected by the granulometry and tidal level. We detected a significant correlation between the abundance of microplastics and meiofauna at those levels, although with a very small estimate. Furthermore, our permutational multivariate tests showed that the abundance of microdebris significantly explained the 39.3% of the variation of the meiofaunal communities at the lowest tidal levels. Conclusions: Our result suggested that microdebris accumulating amongst the beach sand grains negatively impact meiofaunal diversity.  This is not surprising, given that microdebris occupy the same physical space than these animals, presumably modifying the structure of the sediments and the composition of the interstitial water.